Research issues in structured and semistructured database programming : 7th International Workshop on Database Programming Languages, DBPL'99, Kinloch, Rannoch, UK, September 1-3, 1999 : revised papers - Connor, Richard; Mendelzon, Alberto O. (Lecture notes in computer science ;, 2000)
This book constitutes the thoroughly refereed post-proceedings of the 7th International Workshop on Database Programming Languages, DBPL'99, held in Kinloch Rannoch, UK in September 1999. The 17 revised full papers presented together with an invited paper were carefully reviewed and revised for inclusion in the book. The book presents topical sections on querying and query optmization; languages for document models; persistence, components and workflows; typing and querying semistructured data; active and spatial databases; and unifying semistructured and traditional data models.